DUPLEX SCANNING IN CHILDREN WITH CEPHALGIA: POSSIBILITIES, TARGETS AND BENEFITS - V.V. Vasil'chenko; G.A. Karkashadze (Union of pediatricians of Russia, 2006)
Cephalgia is the most frequent complaint in pediatric neurology. Proper diagnostics of underlying cause and, as a consequence, promt adequate treatment could prevent chephalgia chronicity and problems related to it, such as mood changes, reduced ability to work and study and personal development in school age children. One of the leading causes of pediatric cephalgia is cerebrovas cular disorders. Early diagnostics of vascular disorders is essential for adult disability prophylaxis. Nowadays the method of transcranial duplex scanning is used to assess cerebral blood flow giving data to assess blood vessel walls and cavity, surrounding tissues and cerebral hemodynamics as a whole. This method allows to differentiate the causes of cephalgia in children and to administer appropriate treatment in each case. Implementation of duplex scanning as a routine diagnostic procedure in paediatric centers could improve diagnostics and treatment of cephalgia in children.Key words: cephalgia, transcranial duplex scanning, tran scranial dopperography, cerebrovascular disorders, children.